SUSTAINABLE STRATEGIES IN ORGANIC WASTE MANAGEMENT: A SYSTEMATIC LITERATURE REVIEW STUDY - Amri, Husnia Sholihatin; Wurjaningrum, Febriana (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2025)
Introduction: Particularly in Indonesia, waste management—especially organic waste—remains a major worldwide concern. A substantial contributor to greenhouse gas emissions (7.29% yearly) and economic losses of IDR 213–551 trillion, food waste will make up 39.78% of all garbage in 2023. Methods: This study employs a systematic literature review to analyze organic waste management practices and their environmental implications, utilizing secondary data from national and global sources. Results: The findings show that Indonesia has problems with such low public knowledge, reliance on subpar dumps, and limited technology. Locally, creative methods such as using Black Soldier Fly larvae to convert organic waste show promise. Around the world, modern technologies like Malaysian and Thai anaerobic digestion and programs like the European Green Deal show greater efficiency. Successful programs frequently incorporate government incentives, trash segregation regulations, and public education. Conclusion and suggestion: SAccording to the study's findings, managing organic waste sustainably can lower greenhouse gas emissions and help achieve several UN SDGs, such as those related to health, clean water, and climate change. Promoting trash separation at the source, using composting methods, implementing contemporary technologies, and encouraging cooperation between public, corporate, and community sectors are some of the main proposals. Long-term solutions in Indonesia and elsewhere depend on addressing shortages in funding, infrastructure, and public awareness.